Simulation Analysis on The Effect of Different Pressure and Material of Pipe on Pipeline Lifespan in UTHM Biodiesel Plant - RUSDI, MUHAMMAD AMIRUL ASYRAAF (Progress in Engineering Application and Technology, 2022)
The purpose of this analysis is to analyse the durability of a pipe based on the pipe from esterification process to transesterification process at the UTHM biodiesel plant with on different pressure inlets and different materials. The main objective of this analysis is to analyse flow behaviour and stress distribution with different pressure inlets and different materials. Besides that, this analysis also will provide the risk indicator that can be a guideline for scheduled maintenance effects from different materials and different pressure inlets. The software that used in this analysis is Solidworks to design the model and Ansys 19.2 for running the simulation. Only three materials of pipe and two pressure inlets were variable in this simulation. The material is used in this analysis is Stainless Steel, Carbon Steel and Alloy Steel. While two pressure inlet that used in this analysis is minimum pressure inlet 150kPa and maximum pressure inlet 250kPa. Ansys simulation will use a design model that has been designed in Solid Work and there are two types of analysis used in Ansys, namely Fluid Analysis for flow behavior and Structure Analysis for stress distribution. Ansys simulation will use a design model that has been designed in Solid Work and there are two types of analysis used in Ansys, namely Fluid Analysis for flow behavior and Structure Analysis for stress distribution. The result obtained from this simulation, when there is an increase in the inlet pressure, therefore the velocity and pressure of fluid in the pipe also increase. However, the velocity and pressure of fluid are inversely proportional. If the velocity of the fluid increases, the pressure of the fluid will decrease. For the structure analysis result, the lowest Von Mises Stress is Stainless Steel material.